(3eaJGM GdCMcGes - (3GdRGbj, GdcGTGfj, CMeO Hf egOj Hf CHj PQ, J (B1244(3g`s ((3eMeO Hf eMeO Hf jhSa Gdejefjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3Ef ef GdCeQh GdVQhQjI HbGA GdJcGdja GdTQYjI GdaQYjI Edi jhe GdOjf hhLhH GeJKGdgG Ydi cd aQO ef Gdecdajfs
(3BNQgG (B:s
(3BNQgG(B: (3hGdKGfj aj GdJYOj aj eSJfO GdCMcGe Yf GdcJGH hGdSfI Hd Yf GdSfI YfO cKjQ efge hYde MGdI CjkVG ef KHhJ MLjI GdCOdI GdeJbOeI hGdKGdK aj Jhba GdGSJfHGWs
(3JHUQI GdeDda (B:s
(3oPcQ aj GdPQjYI(B: (3GdfQGbjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B1: 260s
(3GdPQjYI, L (B21: 203s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs